Comparative evaluation of effectiveness of autologous platelet rich plasma and intralesional corticosteroids in the management of erosive oral Lichen planus- a clinical study - Upasana Sethi Ahuja; Nidhi Puri; Chandramani B. More; Ritu Gupta; Deepak Gupta (Elsevier, 2020)
Purpose: Oral Lichen planus is a potentially malignant autoimmune disorder, characterized by burning and pain in the affected mucosa which reduces the quality and comfort of patient's life. Various treatment modalities have been documented for OLP but due its malignant potential the alternative therapeutic approaches with least or no side effects are being in demand. One of such, yet unexplored treatment is Platelet rich plasma (PRP). This study aims to evaluate the effectiveness of intralesional PRP as compared to the Intralesional corticosteroids in the management of erosive OLP. Materials and methods: The study sample consisted of 20 clinically and histopathologically confirmed patients of Erosive OLP among which 10 patients were given intralesional corticosteroids and 10 patients were administered intralesional PRP. All the patients were given weekly injections for 2 months and were followed up till 4 months for assessing the parameters such as pain/burning, erythema and size of the lesions. Results: The patients in both the groups showed a statistically significant reduction in all the assessed parameters of erosive lichen planus from baseline till 4 months of treatment and follow up. However, on comparison of the pain reduction, size of lesion and erythema scores between the two groups, the difference was found to be statistically insignificant. Conclusion: The intralesional PRP was found to be of comparative effectiveness with respect to intralesional triamcinolone acetonide in the management of erosive OLP and with an added advantage of having less recurrence and no adverse effects.